2002
DOI: 10.1109/50.974817
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the chirped return-to-zero modulation format

Abstract: We numerically simulated long-distance, high-bit-rate, wavelength division multiplexed (WDM) transmission in dispersion-managed systems. We investigated return-to-zero (RZ) and nonreturn-to-zero (NRZ) modulation formats with amplitude and phase modulation. Consistent with earlier experiments, we find that the chirped return-to-zero (CRZ) modulation format has significant advantages over the NRZ modulation format in WDM systems. We elucidate the physical reasons for these advantages. We then discuss, in detail,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…NRZ is easier to implement, while RZ offers improved receiver sensitivity and tolerance to inter-symbol interference (ISI). NRZ-OOK has a few variants such as chirp-free NRZ-OOK (the most common type), chirped NRZ-OOK [20,66], and duobinary [68]. RZ pulse formats also have several variants, such as chirp-free RZ, chirped RZ (CRZ), CSRZ [35], and p/2 alternate-phase (p/2-AP) RZ [26].…”
Section: Optical Modulation Formatsmentioning
confidence: 98%
“…NRZ is easier to implement, while RZ offers improved receiver sensitivity and tolerance to inter-symbol interference (ISI). NRZ-OOK has a few variants such as chirp-free NRZ-OOK (the most common type), chirped NRZ-OOK [20,66], and duobinary [68]. RZ pulse formats also have several variants, such as chirp-free RZ, chirped RZ (CRZ), CSRZ [35], and p/2 alternate-phase (p/2-AP) RZ [26].…”
Section: Optical Modulation Formatsmentioning
confidence: 98%
“…However, the phase varies within the time span of each pulse, and hence the spectrum is significantly broader. Although the chirp of the pulses can be used to counteract fiber dispersion [5], it generally leads to increased cross-talk penalty and lower overall performance.…”
Section: Chirped Rz (Crz)mentioning
confidence: 99%
“…Numerically, the performance of dispersion-managed 40 Gbit/s TDM-transmission systems over the already installed standard fiber has been analyzed in simulations assuming conventional NRZ and RZ-modulation format with different duty ratios. It is shown that for 40 Gbps TDM-systems, RZ-modulation format with a duty cycle of 0.5 is inherently superior to the conventional NRZ-transmission scheme [24].…”
Section: Introductionmentioning
confidence: 99%